A Prospective Study on Antibiotics-associated Spontaneous Adverse Drug Reaction Monitoring and Reporting in a Tertiary Care Hospital - Andhuvan, Dr. G. (Asian Journal of Pharmaceutics (AJP), 2018)
Background: The aim of the present prospective study was to determine the causality, preventability, and severity of adverse drug reactions (ADRs) occurring in various departments of the tertiary care hospital. Materials and Methods: This prospective, interventional study was undertaken in general medicine, surgery, respiratory medicine, intensive care unit care unit, and nephrology units in a tertiary care hospital, Coimbatore, and to assess preventability, severity, and causality assessment in antibiotics which caused ADRs, and to determine most commonly affected organ system. Results: A total of 143 ADRs were identified in 1138 patients, out of which 74 (51.75%) male patients were identified with ADRs, whereas 69 (48.25%) were female. The age wise distribution revealed that middle-aged patients showed more incidence of ADR 60 (41.96%), followed by geriatrics 41 (28.67%), adult 35 (24.47%), and pediatrics 7 (4.89%). Gastrointestinal tract 66 (46.15%) was the most affected organ system by ADR followed by others 21 (14.7%) skin and appendages disorder 15 (10.48%), central and peripheral system disorder 13 (9.09%), respiratory system disorder 13(9.09%), hematopoietic disorder 4 (2.8%), urinary system disorder 3 (2.09), and CVS 2 (14.7%). Maximum ADRs were reported with beta-lactams class 103 (72.04%) followed by miscellaneous 12 (8.4%), macrolides 10 (6.99%), quinolones 6 (4.99%), and aminoglycosides 5 (4.20%). Conclusion: Antibiotics comprise the major volume of the drug family and in prescriptions of hospitalized patients. Implementation of antibiotic guideline policy in hospitals and strict adherence to it should be ensured for safe and rational use of antibiotics. Furthermore, health system should promote spontaneous reporting of ADRs to regional pharmacovigilance centers which is detected in clinical practice.